2009
DOI: 10.1111/j.1365-2702.2009.02992.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care behaviour and related factors in older people with Type 2 diabetes

Abstract: Implication for nurses highlights the significance of providing patients with social support that will enable them to have good support systems during their disease treatment to enhance self-care abilities and improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
92
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 25 publications
(44 reference statements)
18
92
2
6
Order By: Relevance
“…Diabetes self-management strategies increase lifestyle adjustments to maintain best possible diabetes management to achieve optimal glycaemic control in type 2 diabetics [83][84][85][86][87][88][89][90][91]. In this study the current situation of adherence to self-care behaviour of type 2 diabetics in Arba Minch General Hospital and factors that contribute to efficient adherence to self-care behaviour of diabetics was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes self-management strategies increase lifestyle adjustments to maintain best possible diabetes management to achieve optimal glycaemic control in type 2 diabetics [83][84][85][86][87][88][89][90][91]. In this study the current situation of adherence to self-care behaviour of type 2 diabetics in Arba Minch General Hospital and factors that contribute to efficient adherence to self-care behaviour of diabetics was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies also revealed the negative influences that religious beliefs might play in hindering self-management of illnesses 25,40 . The differences might emerge from how the religious authorities interpret teachings from the scriptures.…”
Section: Religious Beliefmentioning
confidence: 99%
“…Another theme is submission which refers to relinquish self-management to God's will 16 , or to wait for God to heal the condition 16,21,41 . This sometimes manifests as a fatalistic view of illness 25,32,42 , which hinders them in fully self-caring for their condition 1,16,41,43 and not adhering to medication 1,21 . While, to some others being fatalistic do not necessarily have a negative meaning; it gives them inner strength to manage their condition 5 .…”
mentioning
confidence: 99%
“…This left a total of 35 articles included in the review. There were 15 (43%) descriptive or observational studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), 4 (11%) design or development studies (28-31), 3 (9%) quasi-experimental studies (2,32,33), 7 (20%) randomized controlled trials (34)(35)(36)(37)(38)(39)(40), and 6 (17%) qualitative studies (41)(42)(43)(44)(45)(46) included in the review.…”
Section: Methodsmentioning
confidence: 99%
“…Social support is significantly positively correlated with self-care behavior (15,21), taking diabetes medication (13), physical activity (13,26,44), and significantly negatively correlated with diabetes distress (25), as well as reductions in body mass index (39) and HbA1c (2,16,45). Connection is related to improved glycemic control (34), improved depression and quality of life (35), and reductions in HbA1C (31,36,38).…”
Section: Selected Findingsmentioning
confidence: 99%